Funerary practices in the second half of the second millennium BC in continental Atlantic Europe : from Belgium to the north of Portugal - Nonat, L.; Prieto Martínez, M. Pilar, (Archaeopress Archaeology, 2022)
This edited volume presents a selection of essays dedicated to funerary practices from Belgium to the north of Portugal. It aims at filling gaps in the documentation and helping to better understand the relationships between these Atlantic regions during the Bronze Age.